Analysis of the mechanical and wear properties of Calotropis Gigantea Stem Fiber/Flax Fiber as reinforcement epoxy hybrid composites. (2021) - Suresh, A.; Devaraju, A.; Jayakumar, L.
Highlights: In this present experimental work, Calotropies Gigantea Stem fibre (CGS), Flax Fiber (F) and Glass Fiber (G) is used as reinforcing material and reinforced natural fiber composite was fabricated by compression molding method. ASTM standards were followed in the preparation as well as testing of the composite material. The changes of wear and friction performance of the CGS/F fiber composite weight have been investigated. The sudden weight losses appear when increasing the Load. CGS and F fiber composite wear and frictional force was more when we increasing the Load with constant speed and time. Abstract: In the present exploratory work, Calotropis Gigantea Stem (CGS) fiber-Flax Reinforced Natural Fiber Composites were fabricated by Compression Molding Method. The CGS composites were developed by using epoxy resin LY556 as the matrix material and the hardener-HY951 the organic fiber as the Support material. Then, the developed CGS composites were tested to evaluate the mechanical properties such as Tensile Strength, Flexural Strength, and Impact Strength. Additionally, a Pin-on-Disc Wear tester was used for evaluating the wear properties of CGS composite materials. It was found that normal load played an important role in wear as well as friction. In the current investigation, at 30 N load, wear testing pairs exhibit the highest wear loss and high friction.